2016
DOI: 10.1103/physrevlett.117.031802
|View full text |Cite
|
Sign up to set email alerts
|

Search for Narrow Resonances in Dijet Final States ats=8TeVwith the Novel CMS Technique of Data Scouting

Abstract: A search for narrow resonances decaying into dijet final states is performed on data from proton-proton collisions at a center-of-mass energy of 8 TeV, corresponding to an integrated luminosity of 18.8  fb^{-1}. The data were collected with the CMS detector using a novel technique called data scouting, in which the information associated with these selected events is much reduced, permitting collection of larger data samples. This technique enables CMS to record events containing jets at a rate of 1 kHz, by co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
89
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(90 citation statements)
references
References 47 publications
1
89
0
Order By: Relevance
“…The spin-1 mediator scenario via vector or axial-vector interaction is thus highly constrained by the dijet limit for Z search at the Large Hadron Collider (LHC) [23][24][25]. The collider search is yet less sensitive to the detection of spin-0 mediator scenario through scalar or pseudo-scalar interaction as a result of the m 2 q suppression coming from the Yukawa coupling.…”
Section: Jhep01(2018)151mentioning
confidence: 99%
“…The spin-1 mediator scenario via vector or axial-vector interaction is thus highly constrained by the dijet limit for Z search at the Large Hadron Collider (LHC) [23][24][25]. The collider search is yet less sensitive to the detection of spin-0 mediator scenario through scalar or pseudo-scalar interaction as a result of the m 2 q suppression coming from the Yukawa coupling.…”
Section: Jhep01(2018)151mentioning
confidence: 99%
“…A comparison with the dijet cross-section at the Tevatron revealed that signatures from the MW model are orders of magnitude below the QCD background and no constraint emerged for masses below 350 GeV with λ 4 = λ 5 as large as 10 [12]. Existing LHC searches that can be used to compare the MW model with the two jets channel are: ATLAS-8 TeV [23], ATLAS-13 TeV [28], CMS-8 TeV [29], CMS-13 TeV [30]. For example, ATLAS used its 8 TeV data to conclude that color octet scalars are ruled out below 2.8 TeV [23], but as explained above, their benchmark color octet model, that of Ref.…”
Section: A Search For Resonances In Dijets At Lhcmentioning
confidence: 99%
“…The collected data, corresponding to 18.8 fb −1 , were used to perform a dijet resonance search analogous to the one carried out in 2011 [4]. The search results were interpreted as limits on the mass and coupling of a hypothetical leptophobic Z' resonance decaying to quarks.…”
Section: History Of Scouting In Cmsmentioning
confidence: 99%
“…[19] Figure 1: Left: dijet mass spectrum obtained from 18.8 fb −1 of scouting data collected in 2012, with fit to parameterized background function [4]. Right: limits from a variety of collider experiments on the mass and coupling of a hypothetical leptophobic Z'.…”
Section: P H Y S I C a L R E V I E W L E T T E Rmentioning
confidence: 99%